2017
DOI: 10.18632/oncotarget.15713
|View full text |Cite
|
Sign up to set email alerts
|

The cell polarity protein Scrib functions as a tumor suppressor in liver cancer

Abstract: Scrib is a membrane protein that is involved in the maintenance of apical-basal cell polarity of the epithelial tissues. However, Scrib has also been shown to be mislocalized to the cytoplasm in breast and prostate cancer. Here, for the first time, we report that Scrib not only translocates to the cytoplasm but also to the nucleus in hepatocellular carcinoma (HCC) cells, and in mouse and human liver tumor samples. We demonstrate that Scrib overexpression suppresses the growth of HCC cells in vitro, and Scrib d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Indeed, it was previously demonstrated that the loss of apical polarity primes S1 acini into cell cycle entry, but it is not sufficient to enhance proliferation [106]. In addition, depletion of Scrib in the breast, prostate, and liver accelerates tumor progression in the presence of other tumor-driving events but is not sufficient to drive tumorigenesis [104,107,108]. Blocking GJIC in 3-D cultures of S1 cells is not sufficient to enhance proliferation, although it acts in cooperation with extrinsic proliferation signals (Bazzoun/Adissu et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was previously demonstrated that the loss of apical polarity primes S1 acini into cell cycle entry, but it is not sufficient to enhance proliferation [106]. In addition, depletion of Scrib in the breast, prostate, and liver accelerates tumor progression in the presence of other tumor-driving events but is not sufficient to drive tumorigenesis [104,107,108]. Blocking GJIC in 3-D cultures of S1 cells is not sufficient to enhance proliferation, although it acts in cooperation with extrinsic proliferation signals (Bazzoun/Adissu et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also support the idea that disturbance of the three‐dimensional cellular organization can directly support tumor initiation—here in conjunction with the oncogene c‐MYC, which is frequently amplified in human HCCs—and that the cessation of hepatocellular polarity is not merely a consequence of malignant transformation. These findings of our study are supported by a very recent publication showing that Scrib is overexpressed and mislocalized in human HCC …”
Section: Discussionmentioning
confidence: 99%
“…Notably, our results showed strong positive effects of cytoplasmic Scrib on AKT signaling, but not on ERK1/2 or JNK signaling. Different effects were published for breast cancer and liver cells, where Scrib overexpression affected ERK1/2 activation and EMT . It is unclear whether these differences (regulation of AKT or ERK1/2) are due to cell type specific properties or if the differential localization of Scrib allows the regulation of both pathways under specific experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…SCRIB (Scrib) is an evolutionarily conserved component of a common genetic pathway involved in apical-basal cell polarity. Scrib inhibits liver cancer cell proliferation and functioning as a tumor suppressor in liver cancer [ 24 ]. SATB2 (special AT-rich sequence-binding protein 2), known as a nuclear matrix-associated transcription factor and epigenetic regulator, is an evolutionarily conserved transcription factor [ 25 ].…”
Section: Discussionmentioning
confidence: 99%